Reflecting on Basic Art Education in Aguascalientes, Mexico. Implications for Higher Education - Capistrán-Gracia, Raúl Wenceslao (Revista Electrónica Educare, 2018)
The basic art education in Aguascalientes, Mexico, faces a significant number of challenges that must be overcome and problems that must be addressed. Among other challenges, the public education system must train a high number of teachers who lack professional qualifications. The system also has to promote the training of its whole teaching staff and satisfy the demand for sufficient pedagogical materials. Thus, the author proposes that higher education must actively get involved with basic education by implementing remedial programs for unqualified teachers. It also must propose continuous education programs to foster a better preparation of the teaching staff and develop research projects that generate knowledge to promote more comprehensive and better-quality art education. The contributions made to the improvement of art education will impact on more sensitive, creative and harmonious human beings.